2024
DOI: 10.1108/yc-08-2023-1835
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the key drivers in using mobile payment (M-Payment) among Generation Z travellers

Mohd Hafiz Hanafiah,
Muhammad Aliff Asyraff,
Mohd Noor Ismawi Ismail
et al.

Abstract: Purpose The purpose of this study is twofold. The first objective is to identify the factors that affect Gen Z tourists' M-payment behaviour. Next, this study investigates the inter-relationship between Gen Z tourist’s perception of M-payment benefits, adoption behaviour, usage risk and future usage intention. Design/methodology/approach The sample comprised Malaysian Gen Z individuals (n = 326) who had experience using M-payment methods while travelling outbound. Given the complex nature of the model and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…1, Februari 2024: 54-76 that the crowdfunding platform can be used to pay infaq and alms. The results of previous research, such as Chawla & Joshi (2019), Hanafiah et al, (2024), Al-Okaily et al, (2024) and Nguyen et al, (2022) in applying the TAM model explains that trust is defined as an antecedent of perceived ease of use and perceived usefulness which influence attitudes and behavioral intentions to use E-Wallet services and Fintech. In addition, the research results of Muhammad et al, (2022) show that trust is the main factor influencing consumers' willingness to share digital footprints on social media; Shaker et al, (2021) confirmed that trust has a positive influence in predicting intention to follow online restaurant community advice, Abdelwahed et al, (2024) found a significant influence on intention to adoption digital e-health practices among healthcare professionals.…”
Section: Trust and Behavioral Intentionmentioning
confidence: 99%
“…1, Februari 2024: 54-76 that the crowdfunding platform can be used to pay infaq and alms. The results of previous research, such as Chawla & Joshi (2019), Hanafiah et al, (2024), Al-Okaily et al, (2024) and Nguyen et al, (2022) in applying the TAM model explains that trust is defined as an antecedent of perceived ease of use and perceived usefulness which influence attitudes and behavioral intentions to use E-Wallet services and Fintech. In addition, the research results of Muhammad et al, (2022) show that trust is the main factor influencing consumers' willingness to share digital footprints on social media; Shaker et al, (2021) confirmed that trust has a positive influence in predicting intention to follow online restaurant community advice, Abdelwahed et al, (2024) found a significant influence on intention to adoption digital e-health practices among healthcare professionals.…”
Section: Trust and Behavioral Intentionmentioning
confidence: 99%